1974
DOI: 10.1159/000251604
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis and Thrombosis in Behçet’s Disease

Abstract: Venous thrombosis, including superior and inferiorvena caval occlusion is considered an integral manifestation of Behçet’s disease. In this series, 5 of 11 patients (45.4%) with active Behçet’s disease had clinical evidence of present or past venous thrombosis. The mean euglobulin lysis time in the 11 subjects was found to be within the normal range: however, in 3 patients, significant impairment of fibrinolytic activity was demonstrated. Inhibition of systemic fibrinolysis may be a contributory factor in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Diminished fibrinolytic activity has been demonstrated in Behcet's disease and in different clinical types of cutaneous vasculitis by several authors [3,7,8,12,18]. Chajek et al [3] showed an increase of the inhibi tory potential against plasmin as well as against plasminogen activation in the patients' sera.…”
Section: Discussionmentioning
confidence: 98%
“…Diminished fibrinolytic activity has been demonstrated in Behcet's disease and in different clinical types of cutaneous vasculitis by several authors [3,7,8,12,18]. Chajek et al [3] showed an increase of the inhibi tory potential against plasmin as well as against plasminogen activation in the patients' sera.…”
Section: Discussionmentioning
confidence: 98%
“…Although several authors (Kurban & Ryan, 1969;Vaithianathen & Takato, 1968} have found no significant changes in plasma fibritiolytic activity, most authors have found that some patients with a chronic cutaneous vasculitis do have a decreased plasma-fibrinolytic activity (Nilsson, 1967;Cunliffe, 196S;Isacson & Nilsson, 1972a;Parish, 1972;Chajek, Aronowski & Izak, 1973;Sobell, Tabori & Tatarski, 1974)-All our data have been performed on patients who were not overweight, not on drugs and who were fasting; such factors modify plasma-fibrinolytic activity. Fig.…”
mentioning
confidence: 99%
“…BD is a recurrent multisystem inflammatory disorder characterized by vasculitis and arteritis [ 1 , 2 ] and involves blood vessels of all sizes [ 11 13 ]. Conversely, IgAV is defined as vasculitis with IgA1-dominant immune deposits; it affects small vessels, skin, and the gastrointestinal tract and causes arthritis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behçet’s disease (BD) is characterized by recurrent oral and genital ulceration, ocular disease, and several systemic manifestations, including skin lesions, gastrointestinal involvement, neurologic disease, vascular disease, and arthritis [ 1 ]. BD can involve blood vessels of all sizes; hence, most of its clinical manifestations are caused by vasculitis [ 2 ]. In 1963, the first occurrence of proteinuria and hematuria was reported in 13 of 65 BD patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%